Depolarisation of the plasma membrane in the arsenic trioxide (As2O3)-and anti-CD95-induced apoptosis in myeloid cells. - Nolte, Florian; Friedrich, Oliver; ROjewski, Markus; Fink, Rainer; Schrezenmeier, Hubert; Körper, Sixten (Febs Letters, 2004)
Depolarisation of the plasma membrane has been shown to be actively regulated during lymphocyte-apoptosis. Here, we present data about anti-Fas and As2O3 induced depolarisation of myeloid U-937 cells. Anti-Fas but not As2O3-induced depolarisation was significantly dependent on caspase-activation. Na+-fluxes contributed to the depolarisation in early stages of As2O3-induced apoptosis, whereas the membrane potential in late stages depended on Cl- -fluxes. Cl- -channels also played an important role in the induction of cell shrinkage in As2O3-induced apoptosis. However, none of these ions contributed significantly to anti-Fas induced depolarisation. This indicates the existence of different mechanisms for apoptotic plasma membrane depolarisation within one cell type.